SISTEM PENDUKUNG KEPUTUSAN PENCEGAHAN TINDAK KASUS KEJAHATAN DI POLSEK KOTO BARU KABUPATEN DHARMASRAYA MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS - Jeffrey junianto (Perkumpulan Doktor Indonesia Maju, 2022)
Abstract Jeffrey Junianto (1702021018). Decision Support System for the Prevention of Crime Cases at the Koto Baru Police, Dharmasraya Regency Using the Analytical Hierarchy Process Method. Thesis : Department of Information Systems, Faculty of Computer Science, Universitas Dharmas Indonesia, 2021. Dharmasraya Regency is one of the regencies in West Sumatra. As a large district, Dharmasraya has a large population, this causes various social problems in the community such as poverty, unemployment, and others. The existence of social problems encourages some people to commit crimes. Koto Baru Police as one of the existing Polsek in Dharmasraya Regency handles what often happens in the Koto Baru area is the crime of theft, and persecution. This study is intended to explore policing strategies in crime prevention. Therefore, the author collaborates with the Koto Baru Police to create a criminal case prevention system with a decision support system. With this system, it aims to help police officers find data on crime prevention and find out crimes that often occur in the past month. Keywords = Decision Support System, Analytical Hierarchy Process Method, Cyber Crime .